Patience mediates the relationship between mindfulness and pain in patients with cardiovascular diseases. Issue 3 (16th March 2019) - Azizi Ziabari, Leila Sadat; Valikhani, Ahmad; Abouata Amlashi, Mahrooz; Ireland, Michael
ABSTRACT: The aim of the present study was to investigate the mediating role of patience in the relationship between mindfulness and pain among patients with cardiovascular disease. A cross-sectional design was employed. One hundred and ten patients with cardiovascular diseases were conveniently sampled from the clinic of Imam Reza in the city of Shiraz in Iran. Participants completed self-report measures of mindfulness, patience, and pain. Structural equation modeling was performed with Amos 16.0. Results indicated that mindfulness and patience had a significant inverse relationship with pain. There was also a significant positive relationship between patience and mindfulness. Estimated indirect effects showed that patience partly mediated the relationship between mindfulness and pain. These results show that among cardiovascular patients, increases in mindfulness are associated with reductions in pain as a function of increased patience. Therefore, patience is plausibly a key mechanism for understanding the impact of mindfulness on pain reduction.